The Development of Tabeli Media Learning Strategy (Writing Learning Savings) to Improve the Writing Skills for Elementary School Student - Rahmawati, Fitri Puji; Puspita , Eva Bela (Perspektif Ilmu Pendidikan, 2024)
This research aims to develop conventional media in the form of writing learning savings to improve the learning process of cursive writing for grade II elementary school students. The method developed in this research is Research and Development (R&D) using the ADDIE model which consists of the Analysis Stage, Design Stage, Development Stage, Implementation Stage, and Evaluation Stage. Data collection techniques were done by interviews and observation. Meanwhile, the data analysis test used qualitative descriptive analysis by explaining the learning design for cursive writing skills assisted by tabeli media. The validity of the data in this research used triangulation of techniques and sources. According to experts, the results of the assessment and development of the media can be concluded to be suitable as supporting subject for the learning process of cursive writing skills for grade II elementary school students. The level of feasibility of the Tabeli media according to media experts, teacher questionnaires, and small-scale limited trials on grade II students obtained results in the "decent" and "good" categories. So it can be concluded that the Tabeli media is suitable for use as a support for learning to write in cursive order for second-grade elementary school students.